Design and Implementation of an Automatic Control for Two Axis Tracking System for Applications of Concentrated Solar Thermal Power - Hamidi, Saad Tami; Mohammed, Jamal Abdul-Kareem; Reda, Laith Muhsin (Al-Khwarizmi Engineering Journal, 2018)
The present work presents design and implementation of an automated two-axis solar tracking system using local materials with minimum cost, light weight and reliable structure. The tracking system consists of two parts, mechanical units (fixed and moving parts) and control units (four LDR sensors and Arduino UNO microcontroller to control two DC servomotors). The tracking system was fitted and assembled together with a parabolic trough solar concentrator (PTSC) system to move it according to information come from the sensors so as to keep the PTSC always perpendicular to sun rays. The experimental tests have been done on the PTSC system to investigate its thermal performance in two cases, with tracking system (case 1) and without tracking system (case 2). The experimental results showed that the average solar radiation falling on the PTSC prototype in the two cases during the same time was 854 and 701 watt/m2, respectively, which means an increase in the solar radiation about 21.8 % when using tracking system. It was found that the average useful heat gain output of solar collector was equal to (376.2, 252.6 watt) for the two cases, respectively, so there was an increase of about 48.9 % when using the tracking system. Also, the average thermal efficiency of the PTSC was found to be (20.7, 26.5 %) for the two cases, respectively, which means an increase in the average efficiency by 28% with use of tracking system compared to the fixed case.